Can dengue virus be sexually transmitted? - Wilder-Smith, Annelies (Journal of travel medicine, 2019)
Topic: polymerase chain reaction, dengue fever, dengue virus, seminal fluid, public health medicine, vaginal secretions
Gesehen am 28.06.2019